Constructing a valid and reliable higher-order thinking skills assessment for middle school science - Erma Yuliyanti; Yuli Prihatni; Ari Setiawan (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study aims to identify teachers’ needs for a Higher-Order Thinking Skills (HOTS) assessment in science, develop a standardized assessment instrument, evaluate its psychometric quality, and measure Grade 8 students’ HOTS performance. The research employed the Mardapi development model, which includes test specification, item writing, expert review, pilot testing, item analysis, revision, assembly, administration, and score interpretation. Participants consisted of four teachers for needs analysis, six students for readability testing, 95 students for limited trials, and 123 students for large-scale trials. Data were collected through interviews and empirical testing. Item analysis was conducted using item analysis software to examine validity, reliability, discrimination index, difficulty level, and distractor efficiency. The results indicate that HOTS assessment instruments are urgently needed by science teachers. The final product consists of 36 validated multiple-choice items, demonstrating high reliability (0.91), good discrimination, acceptable difficulty levels, and effective distractors. Students’ average HOTS mastery was 56.94% (moderate category), with scores ranging from 16.26% to 97.22%. The instrument is considered valid and reliable for assessing HOTS in lower secondary science.